Effect of Date Pudding on Maternal Energy and the Duration of the Second Stage of Labor - Khadijah, Siti Nur; Indriani, Ririn; Titisari, Ira; Sendra, Eny (Health Access Journal, 2026)
Prolonged second stage of labor contributes significantly to maternal morbidity and increases the need for obstetric interventions. Adequate maternal energy during pushing is essential to prevent prolonged labor. Dates (Phoenix dactylifera) contain approximately 70% carbohydrates in the form of glucose and fructose, which are rapidly absorbed and provide immediate energy. This study aimed to analyze the difference in the mean duration of the second stage of labor between mothers who received date pudding and those who did not. The results demonstrated that the mean duration of the second stage of labor was shorter in the intervention group compared to the control group. Statistical analysis showed a significant mean difference between the two groups (p = 0.030). The homogeneity test indicated equal variances (p = 0.325), supporting the validity of the comparison. These findings suggest that consumption of date pudding during labor is associated with a significantly shorter second stage of labor, indicating its potential benefit as a simple nutritional intervention to support maternal energy during childbirth.